Gender differences in first and corresponding authorship in public health research submissions during the COVID-19 pandemic - Bell, M.L.; Fong, K.C. (My University, 2021)
Objectives. To investigate the rate of manuscript submission to a major peer-reviewed journal (American Journal of Public Health) by gender, comparing periods before and during the pandemic. Methods. We used data from January 1 to May 12, 2020, and defined the start of the pandemic period by country as the first date of 50 or more confirmed cases. We used an algorithm to classify gender based on first name and nation of origin. We included authors whose gender could be estimated with a certainty of at least 95%. Results. Submission rates were higher overall during the pandemic compared with before. Increases were higher for submissions from men compared with women (41.9% vs 10.9% for corresponding author). For the United States, submissions increased 23.8% for men but only 7.9% for women. Women authored 29.4% of COVID-19–related articles. Conclusions. Our findings suggest that the pandemic exacerbated gender imbalances in scientific research. © 2021 American Public Health Association Inc.. All rights reserved.